2004
DOI: 10.1097/00005537-200404000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Schwannoma Surgery Outcomes: Our Multidisciplinary Experience in 400 Cases Over 17 Years

Abstract: Transpetrosal approaches (translabyrinthine, widened retrolabyrinthine) are safe for vestibular schwannoma removal, and rates of postoperative complications and sequelae are decreasing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
2
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(145 citation statements)
references
References 26 publications
6
134
2
3
Order By: Relevance
“…11,75 Frequently cited predictors of facial nerve function include tumor size, surgical approach, and the use of intraoperative monitoring. 15,22,40,64,75 The length of contact of the tumor with the nerve has also been suggested as a potential prognostic factor. 18 Samii et al 74 believe that prior surgery or radiosurgery and the presence of an intratumoral cyst are negative predictors of postoperative facial nerve function.…”
Section: Facial Nerve Functionmentioning
confidence: 99%
“…11,75 Frequently cited predictors of facial nerve function include tumor size, surgical approach, and the use of intraoperative monitoring. 15,22,40,64,75 The length of contact of the tumor with the nerve has also been suggested as a potential prognostic factor. 18 Samii et al 74 believe that prior surgery or radiosurgery and the presence of an intratumoral cyst are negative predictors of postoperative facial nerve function.…”
Section: Facial Nerve Functionmentioning
confidence: 99%
“…In two other large series, Sindou et al [6] and Knosp et al [7] reported a trigeminal and visual cranial nerve deficit incidence of between 14 and 58%. Similarly, even with microsurgical resection with intra-operative monitoring, facial nerve dysfunction occurs in up to 7% of patients [26][27][28][29] and hearing loss is universally observed in most acoustic neuromas exceeding 2-3 cm in diameter [30][31][32]. Hence, radiation therapy has been a preferred choice for such tumors with preserved neurological function.…”
Section: Hypofractionatedmentioning
confidence: 99%
“…They are usually found in the central nervous system, spinal cord, or peripheral nerves of the body, with the most common type being acoustic neuroma. 7 Occasionally, schwannomas occur in the gastrointestinal tract. Together with leiomyoma, leiomyosarcoma, and gastrointestinal stromal tumors (GIST), they constitute mesenchymal tumors of the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%